Vivere, comprendere e agire la catastrofe: Per un uso pubblico dell’antropologia - Falconieri, Irene (Antropologia Pubblica, 2024)
Considering the relation between trust, social change and disasters, this paper presents an analysis of political transformations in a small town in the North-Eastern coast of Sicily, hit by a massive flood on October 1, 2009. The interpretation comes from a voluntary work of counseling carried out with anthropological approach as a prosecution of a Phd research (2010-2013). Both the activities of ethnographic research and political counseling, were characterized by a personal involvement into the local dynamics, in order to apply a possible “public use” of anthropology. During the research and the political action, the ethnographer tried to apply the anthropological theoretical tools to the analysis of a post-disaster setting, with the porpouse of “intervening” actively in the observed sociopolitical processes. A constant effort is request to the anthropologist working in the field to maintain an independent voice.